Die Evaluation des ESF-BA-Programms am Beispiel der Förderung beruflicher Weiterbildung - Axel Deeke; Thomas Kruppe (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– Active labour market policy under the terms of Volume III of the German Social Code is being subsidized by the European Social Fund within the scope of the 'ESF-BA programme' from 2000 until 2008. First of all, participation in vocational training schemes is facilitated by ESF subsistence allowances paid to unemployed persons who are not entitled to subsistence benefits by law. Furthermore, occupation-oriented training schemes were offered as supplementary ESF modules within the programme, which were not eligible according to the German Social Code Volume III. One main focus of research conducted by the Institute for Employment Research (IAB) in parallel with the ESF-BA programme is the evaluation of measures to promote vocational training funded by the ESF in comparison to existing statutory promotion schemes (evidence of 'added value') and the 'counterfactual' non-participation in measures. The main benchmark for evaluating ESF-funded training schemes is employability, the impact of which is analyzed by comparing participants in measures with groups of non-participants with similar characteristics. The evaluation is empirically based on the administrative process-generated data of the Federal Employment Agency and a national representative survey of participants in measures funded by the ESF from 2000 to 2002 and comparison groups (participants without ESF-funding and unemployed non-participants). Both the heterogeneity of participant groups funded by the ESF and of schemes conducted in East and West Germany is demonstrated with a descriptive analysis of the survey data. Multivariate analyses of the transition from ESF-funded vocational training to subsequent employment verify that the structural mismatch on the labour market, which particularly affects priority groups targeted by the ESF, cannot be balanced by occupational training schemes. Impact analyses of comparison groups are based on process-generated and survey data selected by the method of sequential matching. The share of participants who continue to work in 'non-funded employment liable to social security' as well as 'funded and non-funded employment including funded self-employment' after completing the programme is analyzed to indicate the performance of ESF-funded training schemes. Finally, it is investigated whether registered unemployment is likely to be terminated faster by participants in measures.
Keywords: 330; Weiterbildungsförderung - Erfolgskontrolle; europäischer Sozialfonds - Programm; Beschäftigungsfähigkeit; arbeitsmarktpolitische Maßnahme; berufliche Reintegration